THE IMPACT OF GLOBALISATION ON PESANTREN EDUCATION - Elyati, Eni (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
Globalisation has both positive and negative impacts on the development of pesantren. Pesantren is an Islamic educational institution in Indonesia. The role of Islamic education, especially in pesantren in this era of globalisation, is to be ready to accept and face technological developments and advances that mostly come from foreign countries. Pesantren must make reforms and changes in order to create strong generations, generations that have broad knowledge and are able to develop knowledge derived from the Qur'an and Hadith. So as to be able to make a generation that is not only successful in religious matters, but is able to face the advancement of science and technology in the era of globalisation. Pesantren must be able to face the era of globalisation, which was originally a challenge and obstacle to become a golden opportunity for the development of Indonesian society. Of course, pesantren must process and change according to the needs of global society by not leaving old traditions that are still considered good.